2012
DOI: 10.1210/jc.2011-0618
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Occurrence ofBRAFV600EIs a Rare Clonal Event in Papillary Thyroid Carcinoma

Abstract: These data demonstrate that clonal BRAF(V600E) is a rare occurrence in PTC, although frequently this cancer consists of a mixture of tumor cells with wild-type and mutant BRAF. These results suggest that BRAF mutation in PTC is a later subclonal event, its intratumoral heterogeneity may hamper the efficacy of targeted pharmacotherapy, and its association with a more aggressive disease should be reevaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
115
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 37 publications
10
115
2
1
Order By: Relevance
“…In our training set, 82.3% of the population conventionally showed the BRAF mutation, which is consistent with previous Korean studies (Chung et al 2006, Kim et al 2009, Jung et al 2010. The BRAF positivity rate appears to be higher in our study than in other studies performing a quantitative analysis of BRAF mutations (Guerra et al 2012a,b, Gandolfi et al 2013. As the incidence of BRAF mutation in PTCs varies Using a conventional approach, there was no significant association of BRAF positivity with clinical/ pathological parameters other than the presence of extrathyroidal extension and the absence of thyroiditis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our training set, 82.3% of the population conventionally showed the BRAF mutation, which is consistent with previous Korean studies (Chung et al 2006, Kim et al 2009, Jung et al 2010. The BRAF positivity rate appears to be higher in our study than in other studies performing a quantitative analysis of BRAF mutations (Guerra et al 2012a,b, Gandolfi et al 2013. As the incidence of BRAF mutation in PTCs varies Using a conventional approach, there was no significant association of BRAF positivity with clinical/ pathological parameters other than the presence of extrathyroidal extension and the absence of thyroiditis.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of the BRAF mutation in tissues was considered important in the analysis. However, the subclonality of the BRAF mutation in PTCs has recently been suggested (Guerra et al 2012a). In this context, the quantification of the mutated allele was emphasised in terms of predicting prognosis (Guerra et al 2012b); however, several studies have shown results contradictory to those findings, as determined by the quantification of mutated alleles (Gandolfi et al 2013) and immunohistochemical (IHC) staining (Ghossein et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies report an association of BRAF V600E mutation with a more aggressive behavior (13,16,17,20,22), others, including the present series, failed to document such association (14,18,19,21). These apparently conflicting results have to be reevaluated in light of a recent study (38) demonstrating that clonal occurrence of BRAF mutation is a rare event in PTC and that more frequently this mutation affects only a subpopulation of cells. Additional alterations might be necessary to sustain transformation in BRAF V600E-positive tumors.…”
Section: Discussioncontrasting
confidence: 65%
“…Mutual exclusivity in PTCs of the most common genetic mutations, including BRAF and RAS mutations and RET/PTC rearrangements, indicate that each event is self-sufficient to constitutively activate the tumor-initiating MAPK pathway [6]. Conversely, more recently, a study that used pyrosequencing to determine the percentage of mutant BRAF alleles in conventional PTCs concluded that BRAF V600E is a rare clonal event and more often a nonclonal mutation, occurring late during PTC progression [7]. If confirmed, this finding would have important ramifications because it would undermine the rationale for using therapies targeted against this oncoprotein.…”
mentioning
confidence: 99%